Criteria for selecting plants for a plant-microbial fuel cell - Besarab, Y.V. (Problems of Environmental Biotechnology, 2023)
Understanding the processes of photosynthesis in plants and selecting the most efficient photosynthetic plant species are key aspects in selecting suitable plants for use in a plant-microbial fuel cell. This is especially important, since the amount of rhizosediments affects the result of bioelectricity production. More promising types of plants for use in plant-microbial fuel cells (PMFC) have been identified.